A Critique on the Book The Basics of Neuroleadership: Organizational Leadership by Neuroscience - Elmira Shakeri; Karim Esgandari; Shadi Orafaye Jamshidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Critique of academic books causes due care to be taken in their proper organization. Accordingly, the purpose of this article is to critique the book of The Basics of Neuroleadership: Organizational Leadership by Neuroscience, by Kiumars Ahmadi and published in 2018 by the Termed Press. The method of evaluation and critique of this work is citation-analytical and in accordance with the model proposed by the Council for the Study of Humanities Texts and Books in the framework of general introduction, form and content study of the work. According to the findings, the strengths of the book include the innovation in the subject and its interdisciplinary and typography, quality of printing, the content congruence with the principles and Foundations of religion and Islam. Shortcomings of this book includes that the text is not that much fluent and eloquent. There are some necessary headlines completely missed in the text. Overall, in spite of its Excellency, the book is needed to be revised and edited in order to be applied as an educational textbook.